Generation of two isogenic human iPSC lines (ZIPi013-B-1, ZIPi013-B-2) carrying a CRISPR/Cas9-mediated deletion of TRPM4 - Undine Haferkamp; Narasimha Telugu; Kim Krieg; Wiebe Schaefer; Dennis Lam; Lars Binkle-Ladisch; Manuel A. Friese; Sebastian Diecke; Ole Pless (Stem Cell Research)
Two isogenic hiPSC lines, ZIPi013-B-1 and ZIPi013-B-2, were generated by CRISPR/Cas9-mediated indels in the TRPM4 gene of the previously published ZIPi013-B. TRPM4 belongs to the evolutionarily conserved family of transient receptor potential (TRP) channels. It is expressed ubiquitously and its activity is regulated by intracellular calcium binding, changes in membrane potential, phosphoinositide lipids in the plasma membrane and the local concentration of cytoplasmic ATP and ADP. TRPM4 has been implicated in various diseases, including neurological and immune system disorders, cardiac diseases and cancer. Both new cell lines offer the opportunity to model human diseases and test therapeutic modalities addressing these.